2016
DOI: 10.1371/journal.pone.0165951
|View full text |Cite|
|
Sign up to set email alerts
|

E2F1 and TFDP1 Regulate PITX1 Expression in Normal and Osteoarthritic Articular Chondrocytes

Abstract: We previously reported a loss-of-PITX1 expression in patients suffering of knee/hip osteoarthritis (OA). Search for the mechanism underlying this event led us to discover that PITX1 repression was triggered by the aberrant nuclear accumulation of Prohibitin (PHB1), an E2F1 co-repressor, in OA articular chondrocytes. In the current study, we assessed in details the involvement of E2F transcription factors in regulating PITX1 expression. We also analyzed other genes that are similarly regulated by E2F in regard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“… 55 The E2F1-regulated protein PITX1 is an important regulatory factor whose inhibition can promote chondrocyte apoptosis. Pellicelli et al 20 demonstrated that inhibition of E2F1 suppressed PITX1 promoter activity and mRNA transcription in normal and OA articular chondrocytes. Downregulation of E2F1 has been associated with increased apoptosis of articular chondrocytes and OA deterioration, 56 , 57 while reduction of PITX1 synthesis and activity can lead to excessive lysis of chondrocytes, an important marker of articular cartilage degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 55 The E2F1-regulated protein PITX1 is an important regulatory factor whose inhibition can promote chondrocyte apoptosis. Pellicelli et al 20 demonstrated that inhibition of E2F1 suppressed PITX1 promoter activity and mRNA transcription in normal and OA articular chondrocytes. Downregulation of E2F1 has been associated with increased apoptosis of articular chondrocytes and OA deterioration, 56 , 57 while reduction of PITX1 synthesis and activity can lead to excessive lysis of chondrocytes, an important marker of articular cartilage degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The promoter activity and mRNA transcription of PITX1 (paired-like homeodomain transcription factor 1) have been shown to be regulated by E2F1 in OA chondrocytes. 20 However, the potential regulatory influences of miR-34a on E2F1, PITX1, and chondrocyte apoptosis remain to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Other than its function in cancer progression, induced levels of TFDP1 and its partner E2F were also observed in rat hippocampus after global cerebral ischemia together with its dimerization partner, the Rb binding protein, E2F1 (Jin et al, 2001). Lastly, knockdown of TFDP1 was found to reduce PITX1, whose loss of expression has been reported in patients suffering from osteoarthritis, a type of joint inflammation (Pellicelli et al, 2016).…”
Section: Transcription Factor Dp1 (Tfdp1) As a Possible Regulator Of Brain Agingmentioning
confidence: 81%
“… 16 Meanwhile, E2F1 is involved in the regulation mechanism of OA. 17 However, there are few reports on whether KDM2A regulates E2F1 and participates in knee OA. This led us to explore the regulatory mechanism of KDM2A and E2F1 in knee OA.…”
Section: Resultsmentioning
confidence: 99%
“… 16 Interestingly, E2F1 has been implicated in the regulation mechanism of knee OA due to its potential in modulating articular chondrocytes. 17 Moreover, E2F1 can elevate the transcription of its downstream target gene, pituitary tumor transforming gene 1 (PTTG1), 18 which can promote OA progression. 19 Therefore, we aimed to delineate a hypothesized mechanism by which miR-31-mediated effects on the KDM2A/E2F1/PTTG1 axis exert regenerative effects on cartilage during OA.…”
Section: Introductionmentioning
confidence: 99%